Regenerative biology and medicine - Stocum, David L. (Elsevier/Academic Press, 2012)
Suitable for investigators in chemistry, computer science, informatics, physics and mathematics as well as graduate students, clinical physicians, and biologists who are realizing the importance of the fields of regenerative biology and medicine in practice, this title includes coverage of skin, hair, teeth, cornea, and central neural tissues.